(3CTYGQ GdfSGAs - (3eMeO Hf YeQGf Hf ehSi, CHh YHjO Gddg GdnerQoRHGfj,J (B384 (3g` s
(3ChdgG (B:s
(3CNHGQ djdi eY GdfGHZI GdLYOi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B319 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B97s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B21 - (3U (B423 s
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs